ANALYSIS OF THE EFFECT ON THE MECHANICAL PROPERTIES OF THE LASER CUTTING AIRCRAFT SKIN - PENG YuHai; HOU HongLing; ZHANG Hui; XIE YuKun; PENG Kai (Jixie qiangdu)
Laser cutting technology is widely used in manufacturing industry. But the laser absorptivity of the aircraft skin material is low,and the laser cutting quality is poor,so laser cutting is not applied in manufacturing of the aircraft skin. In order to searching laser cutting performance of the aircraft skin and the change of its mechanical properties by laser cutting,the surface topography analying,micro-hardness testing and tension,compression and shear test were carried used laser cutting test sample.The test result show that the test sample emerged freeze slag after laser cuting,and its tensile strength decreased slightly,but compression strength shear strength retained original level. So laser cutting technology can be used in edge manufacturing of the aircraft skin by improving the laser cutting process and rising the laser cutting quality.